2018
DOI: 10.2478/jtim-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C screening in commercially insured U.S. birth-cohort patients: Factors associated with testing and effect of an EMR-based screening alert

Abstract: Background and ObjectivesHepatitis C virus (HCV) testing rates among U.S. birth-cohort patients have been studied extensively, limited data exists to differentiate birth-cohort screening from risk- or liver disease-based testing. This study aims to identify factors associated with HCV antibody (HCV-Ab) testing in a group of insured birth cohort patients, to determine true birth cohort testing rates, and to determine whether an electronic medical record (EMR)-driven Best Practice Alert (BPA) would improve birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Accessing the EHR tool facilitates the health care delivery,19,24 made more accurate decisions,22 and contributes to the health care quality improvement and research output47,48 at reduced cost 49,50. The tool also ensures the safe transfer of health care data that meets the patient’s expectation,51 supports the continuity of patient care,11 and maintains the compliance with medication adherence 52,53. Moreover, the tool helps diabetes goal achievement, while the service delivery process is assisted from non-physician workers 54…”
Section: Discussionmentioning
confidence: 99%
“…Accessing the EHR tool facilitates the health care delivery,19,24 made more accurate decisions,22 and contributes to the health care quality improvement and research output47,48 at reduced cost 49,50. The tool also ensures the safe transfer of health care data that meets the patient’s expectation,51 supports the continuity of patient care,11 and maintains the compliance with medication adherence 52,53. Moreover, the tool helps diabetes goal achievement, while the service delivery process is assisted from non-physician workers 54…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the recent publication by Yeboah-Korang et al . titled “Hepatitis C screening in commercially insured US birth-cohort patients: Factors associated with testing and effect of an EMR-based screening alert.”[1] We were pleased to read efforts of Yeboah-Korang et al to improve HCV testing for the 1945–1965 birth cohort in accordance with national HCV screening recommendations. Although the authors found that a physician-facing electronic medical record (EMR) best-practice alert (BPA) increased HCV testing a significant amount, the rate of testing after implementation remained low at 10%.…”
mentioning
confidence: 99%
“…Physician-based EMR prompts, such as the one implemented by Yeboah-Korang et al , have shown mixed results. [1, 2, 3, 4, 5] We are optimistic that complementing physician-based BPAs with patient education and engagement would further improve HCV testing in healthcare settings.…”
mentioning
confidence: 99%
“…A variety of interventions have been proposed to increase screening and uptake rates across the United States, with mixed results. We recently reported an improvement of HCV screening rates from less than 1% to over 10% at our institution within a few months after implementation of a systemwide, electronic medical record (EMR)-based best practice alert (BPA) ( 10 ). The aim of this study was to evaluate the longer-term impact of the HCV BPA on HCV birth-cohort screening rates and to study the test implementation rates of individual primary care physicians (PCPs).…”
Section: Introductionmentioning
confidence: 99%